PENGARUH LATIHAN QUICK LEAP TERHADAP POWER OTOT TUNGKAI TIM BOLA VOLI PUTRA SMAN 1 KECAMATAN PINGGIR - Fajar Rahmat Syahputra; Slamet Slamet; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstrack: The problem in this research is that when smashing the ball often touches the net and doesn't even cross the net. In addition, when doing a smash block from an opponent the ball is often on top of the block, making it easier for the opponent's smash to enter the defensive area. This type of research is a type of experimental research to see the effect of the form of exercise. The purpose of this study was to see the effect of Quick Leap training on leg muscle power of the men's volleyball team at SMAN 1 Pinggir District. The population in this study was the men's volleyball team at SMAN 1 Pinggir District, amounting to 10 people. The sampling technique is using total sampling, where the total population is sampled. The data collection technique was obtained from the pre-test and post test. The instrument in this study used a vertical jump as a tool for measuring leg muscle power. After that, the data were processed statistically, to test for normality using the Lilifours test at a significant level of 0.05α. The analysis was performed using the t-test, it can be concluded that there is an effect of Quick Leap training on the leg muscle power of the men's volleyball team at SMAN 1 Pinggir District as evidenced by the Tcount of 2.069 and Ttable 1.833. Means that tcount> ttable. At the level ɑ = 0.05.Key Words: Quick Leap Exercise, Leg Muscle Power